Analysis of Factors Affecting Tourist Visits at Taipa Beach, North Palu District [I] - Buyung Cintaury; Eko Jokolelono; Andi Herman Jaya (Jurnal Mantik, 2021)
This research aims to find out the factors that influence tourist visits in Taipa Beach North Palu Sub-District, knowing the characteristics of tourists and the tourist conditions of Taipa Beach North Palu Sub-District. This study used primary data sourced from the dissemination of questionnaires to 40 visitors to Taipa Beach North Palu Sub-District..Analysis data used is multiple linear regressionanalysis. The number of tourist visits as dependent variables and three independent variables are variable income, travel expenses, and facilities. The results of the analysis showed variable income had a positive and significant effect, travel costs had no significant effect, facility variables had a positive and significant influence. And it is known that the minimum cost incurred by visitors to visit Taipa Beach tourism is IDR 80,000.